Embedded acoustic long baseline localization system for autonomous underwater vehicles - Redouane Es-sadaoui; Jamal Khallaayoune; Tamara Brizard (Institute of Advanced Engineering and Science, 2021)
The attenuation of global positioning system (GPS) in water medium makes localization of autonomous uderwater vehicles (AUVs) particularly challenging. The long baseline (LBL) positioning system can extend GPS using beacons as references. This work aims at building an acoustic LBL-based system able to localize AUVs operating in swarms thanks to a small size acoustic transceiver embedded onboard AUVs and implementing range-based localization algorithms to estimate the swarm coordinates in real-time. The distances computation between navigating AUVs and fixed beacons were implemented in a digital signal processor (DSP) which computes the time-of-arrival (ToA) of incoming pure tone acoustic waves. The principle of design, hardware architecture, implementation, simulations and sea experiments are described in this paper. The experimental data showed an average deviation around 0.62 m when an AUV is placed at 45 m far away from a beacon. This deviation increases with distance: around 4.8 m measured at 500 m. This performance can be improved by taking into consideration the two main factors examined in this paper, which are sound velocity profile and propagation model.